Psycho Krieg im Klassenzimmer - Heinrich, Annette; Steinbrecher, Michael (Germany, 2007)
Alexander and Samantha are two children who have been abused by their fellow classmates for years both psychologically and physically, wile their environment helplessly assisted to this although the parents knew that something was wrong with the children. Years later they both managed to overcome the memory of these tortures however, will the wounds of the abuse ever heal?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films